2008
DOI: 10.1093/humrep/den110
|View full text |Cite
|
Sign up to set email alerts
|

A distinct cohort of the TGFβ superfamily members expressed in human endometrium regulate decidualization

Abstract: BACKGROUNDSuccessful blastocyst implantation requires the differentiation of human endometrial stromal cells (HESC), a process known as decidualization. Activin A, a transforming growth factor β (TGFβ) superfamily member, enhances HESC decidualization and localizes to decidual cells in human endometrium. Other TGFβ superfamily members, including BMP2, BMP4, BMP7, GDF5, GDF8, GDF11, TGFβs and Nodal, may also play a role during decidualization. This study aimed to identify these TGFβ family members in human endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 56 publications
3
65
1
2
Order By: Relevance
“…NODAL was also undetected in human endometrial stromal cells (HESC) in vitro when examined in both the non-decidualized and decidualized state. These results support the aforementioned data as the HESC were derived primarily from secretory phase uterine biopsies (day 10-21) and contain 97% pure stromal cells (Stoikos et al 2008). The absence of NODAL expression and immunoreactivity during decidualization is especially interesting considering the striking decline of NODAL mRNA during the secretory phase in humans (which decidualize in each cycle) and the banding pattern that shows decreased Nodal expression at the implantation site in mice (which only decidualize locally in the presence of the implanting blastocyst).…”
Section: Humansupporting
confidence: 88%
See 1 more Smart Citation
“…NODAL was also undetected in human endometrial stromal cells (HESC) in vitro when examined in both the non-decidualized and decidualized state. These results support the aforementioned data as the HESC were derived primarily from secretory phase uterine biopsies (day 10-21) and contain 97% pure stromal cells (Stoikos et al 2008). The absence of NODAL expression and immunoreactivity during decidualization is especially interesting considering the striking decline of NODAL mRNA during the secretory phase in humans (which decidualize in each cycle) and the banding pattern that shows decreased Nodal expression at the implantation site in mice (which only decidualize locally in the presence of the implanting blastocyst).…”
Section: Humansupporting
confidence: 88%
“…NODAL protein was, however, still detectable around the luminal and glandular epithelium at a steady state throughout all phases of the menstrual cycle (Papageorgiou et al 2009). In the context of decidualization, an earlier study by the same investigators explored the roles of numerous TGFB superfamily members during decidua formation (Stoikos et al 2008). Intriguingly, NODAL protein was not observed in mid-to late-secretory endometrial samples as would be reported in Papageorgiou et al (2009).…”
Section: Humanmentioning
confidence: 91%
“…Elevated activin concentrations have been linked to reduced adhesion of the blastocyst to the LE (Stoikos et al 2008). However, others have found higher concentrations of activin A in uterine fluid collected during the periovulatory period in women who became pregnant after intrauterine insemination compared to those that failed to establish a pregnancy (Florio et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…TGF beta 1 is essential in many reproductive processes (Jones et al, 2006), respectively, in normal endometrial decidualisation processes (Stoikos et al, 2008). Earlier studies have established the role of the TGF family in trophoblast invasion and have shown absence of TGF beta 1 in villous trophoblasts (Lyall et al, 2001;Simpson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%